2020
DOI: 10.1111/ajd.13435
|View full text |Cite
|
Sign up to set email alerts
|

Prurigo pigmentosa: An institutional retrospective study of 24 patients

Abstract: abnormal transient elastography. No correlation for gender, cumulative dose, age, duration of treatment or presence of psoriatic arthritis was found.Our population is very overweight which is reflected in our number of failed tests (36.2% of 105). These results are similar to previous findings in NZ (25% in 133 patients) and Ireland (35% in 77 patients). 5,6 Like many other studies, obesity was associated with abnormal TE results. It is unsurprising that 14 of our 15 patients with severe liver fibrosis had NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The resolving lesions were characterized by crusted papules and the late lesions were characterized by reticulate hyperpigmentation. 2 , 9 , 10 Our study showed the lesions of PP could be focal or multifocal, but most of them were symmetrical. Lesions of different stages often presented at the same time in the same patient, which revealed how the lesions develop.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The resolving lesions were characterized by crusted papules and the late lesions were characterized by reticulate hyperpigmentation. 2 , 9 , 10 Our study showed the lesions of PP could be focal or multifocal, but most of them were symmetrical. Lesions of different stages often presented at the same time in the same patient, which revealed how the lesions develop.…”
Section: Discussionmentioning
confidence: 62%
“…The fully developed lesions were characterized by papules, papulovesicles forming reticular distribution. The resolving lesions were characterized by crusted papules and the late lesions were characterized by reticulate hyperpigmentation 2,9,10. Our study showed the lesions of PP could be focal or multifocal, but most of them were symmetrical.…”
mentioning
confidence: 63%
“…Prurigo pigmentosa is a rare disease affecting typically women in the second and third decades. 1 Initially, the patient presents a rapid onset of inflammatory papules on the chest and back, which spread over the trunk in a few weeks with a reticulate pattern, becoming crusted and necrotic.…”
mentioning
confidence: 99%